The Implementation of Short Animation Films to Enhance Students' English-Speaking Performance - Mantulameten, Wenny E. (Huele: Journal of Applied Linguistics, Literature and Culture, 2023)
This library research examines the implementation of short animation films as an instructional medium for developing EFL students' speaking performance. Through analysis of theoretical foundations and empirical studies, this research investigates three key aspects: the impact of animation films on speaking skills, effective implementation strategies, and solutions to common challenges in classroom practice. Findings indicate that animation films significantly enhance speaking performance through improved pronunciation accuracy, vocabulary acquisition, and speaking confidence when implemented systematically. Successful implementation requires careful consideration of pre-viewing preparation, structured viewing activities, and post-viewing tasks that maximize speaking practice. While technical constraints and pedagogical challenges exist, these can be effectively addressed through proper resource management and structured teaching frameworks. This study contributes to the understanding of multimedia integration in language teaching by providing evidence-based insights for practitioners implementing animation films in speaking instruction.